Peningkatan Mutu Kayu Rajumas (Duabanga moluccana) Melalui Modifikasi Panas - Sulthanulmufti, Sulthanulmufti; Wulandari, Febriana Tri; Ningsih, Rima Vera (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
Research on improving the quality of rajumas wood (Duabanga moluccana) through heat treatment aims to determine the effect of heat treatment on the physical and mechanical properties of rajumas wood. This study used an experimental method with an experimental design in the form of a non-factorial complete randomized design, namely the temperature factor with the treatment of three temperature variations of 140oC, 160oC, 180oC and three replications. Heat treatment carried out in this study caused changes in the three parameters of the physical properties of rajumas wood tested, namely moisture content, density, and dimensional stability. Changes in the physical properties of wood occurred in all three variations of treatment temperature (140oC, 160oC, 180oC). Heat treatment results showed a positive response that can improve the physical properties of rajumas wood. Heat treatment showed an increase in MoE and MoR wood mechanics properties as the treatment temperature increased. The use of 160oC heating temperature gives the highest MoE and MoR improvement results and the use of higher heating temperatures will reduce wood mechanics. Heat treatment method can be an effective method in improving wood properties.